Inclusive Education Believes and it’s Effects on the Education of Children with Physical Disabilities in Secondary Schools in Buea, Cameroon - Dr. Ambei Ruhama Faizefu (International Journal on Integrated Education, 2022)
This study was designed to investigate “Inclusive education believes and its effects on the education of children with physical disabilities in the Buea municipality”. The objectives that were used for the study were; to examine the impact of cultural believe about inclusion on the education of children with physical disabilities in the Buea municipality, to examine the impact teachers believe about inclusion on the education of children with physical disabilities in the Buea municipality and to examine the impact of family believe about inclusion on the education of children with physical disabilities in the Buea municipality. The sample size was 60 students selected from three secondary schools in Buea municipality. The questionnaire was used to obtain information from correspondents and data were analyzed using percentages and frequencies. The following results were obtained; cultural believe about inclusion, teachers believe about inclusion and family believe has a positive role on the education of children with physical disabilities in the Buea municipality. Based on the above result, the following recommendations were obtained; teachers, counselors, parents, should assist students to make use of teaching materials in teaching.